Contributions to investigate construction management without losses - Rojas Julian, Paula (Universidad Nacional de Ingeniería, 2018)
In this essay we present a review of various contributions to improve the production of the infrastructure industry, by applying the Lean construction model (construction without losses); because it has been detected that, currently, in most of the productive activity of the sector under study they lack planning, control and monitoring, and, above all, the issue of quality. Considering that we live in times of abundant knowledge and information, for that reason, we highlight the importance of Construction Management as a research line to improve the quality of the industry in this field; for this, it is necessary to inquire about labor control, the types of works in the construction items, the balance sheets, the planning and programming of works, the human resources management that participates in the execution of works, the control of waste in the subject of transport, logistics, materials, etc.